MEDIASOCIALIZATION OF YOUNG PEOPLE IN MODERN MEDIA SPACE - Olena Kolomiets (Kherson State University, 2018)
The development of the information society causes a new direction of socialization - media socialization, especially it's relevant for young people, who is an active media consumer. The essence of the notions of «media space», «media socialization», «cyber socialization» are analyzed in the article. The features of the media space functioning are considered, taking into account the factors of socialization, its functions are represented in accordance with the traditional socialization process. The influence of the media on the socialization process is determined as a condition for the further development of the components in the youth media socialization. The principles of youth media socialization in the conditions of media space are offered (system, activity, bilateral interaction of personality and virtual reality, media activity and critical thinking). The components of the media-socialization process are presented (forms, mechanisms, agents of media-socialization, etc.). The indicators of successful and unsuccessful media socialization are indicated. The basic conflict of media socialization is determined, which affects its result (the balance of virtual and real). The media socialization criteria with corresponding levels of development and indicators is offered in the article (media adaptability, media autonomy, media activity). The levels of media-socialization of youth are presented in conditions of modern media space. The study of the process of youth media socialization was confirmed by the high percentage of respondents with low (38.5%) and medium (41.8%) levels of media-socialization. At the same time, the high level of media-socialization was characteristic only for 19.7% of respondents. The issue of media socialization of young people becomes acute in connection with the situation that has developed in the state. The system of social education institutions faces the challenge of initiating changes in young people entering into the media space, which in the future will create effective conditions for development taking into account media resources. The problem of youth media socialization is not limited to the research conducted. Promising areas of scientific research can be: development of socio-pedagogical conditions and technology of media-socialization of the individual; development of methodical support for the implementation of media-socialization technology in general educational institutions; introduction of foreign experience of youth media socialization into practice of social work.